Comparing the impact of in-person vs. virtual 10-week family-based childhood obesity management program on anthropometric, cardiometabolic, and mental health outcomes - Heidl, Alexandra J.; Sun, Daisy; Faustini, Claudia; Gierc, Madelaine; Bains, Andy; Cohen, Tamara R. (Frontiers in Pediatrics, 2025)
ObjectivesTo compare differences in patient outcomes in individuals living with overweight and obesity who attended a 10-week multidisciplinary program delivered virtually vs. participants who completed the program in-person.MethodsData from 27 youth (8–18 years old) who attended virtual programming were matched by sex and body mass index (BMI) z-scores to youth who completed in-person programming. Changes in anthropometric, biomarkers (glucose, lipids and liver enzymes) and mental health (Beck Youth Inventories, Second Edition; “BYI-2”) were compared across groups.ResultsBMI z-scores did not differ between groups (p = 0.88). Cardiometabolic measurements showed no significant differences at 10-weeks for any parameter, and there were no significant differences in BYI-2T-scores across groups (p > 0.05).ConclusionThe mode of delivery of a pediatric multidisciplinary family-based program was not associated with significant differences in participant outcomes, suggesting that both modes of delivery are effective.